The Influence of Green Product and Green Advertising on Purchasing Decisions: A Case Study of The Body Shop - Sinaga, Radika; Yunita, Nindya; Mulia Utama, Amrin (Journal of Management and Business Innovations, 2025)
This study analyzes the influence of sustainable products and environmentally friendly advertising on consumer purchasing decisions at The Body Shop in the Medan Johor District. A quantitative method was used with a population of 154,096 people. Based on the Slovin formula with a tolerance of 10%, 100 respondents were obtained through purposive sampling. Data was collected using a Likert scale questionnaire. Analysis was conducted using SPSS 27, including validity, reliability, normality, multicollinearity, heteroskedasticity, multiple linear regression, t-test, F-test, and the coefficient of determination R². The results indicate that sustainable products have a significant positive influence on purchasing decisions. Eco-friendly advertising was also found to have a significant positive influence on consumer purchasing decisions. Both independent variables simultaneously and significantly influence purchasing decisions. Practical Implications: Cosmetics companies need to optimize sustainability elements in product development and promotional strategies. Focusing on environmental value communication can enhance consumer appeal and drive purchases. These findings provide strategic guidance for management in developing effective sustainable marketing approaches.Keywords: Green Advertising, Green Product, Purchase Decision